#TITLE_ALTERNATIVE# - SAUT H. SINAGA (NIM 10203012), HARRYANTO
Numerical modeling is the basic method to determine the growth process that is happen in the geothermal reservoir. Mathematical modeling with finite difference method one phase in numerical approximation is uses with some physical parameter. Darcy's law, Mass Equilibrium, and Energy Equilibrium equation are the basic equation that is used in this paper. Heat source from magma will flow through the fractured zone, whereas this zone has different permeability and porosity characteristic from the other area around the fractured zone, and conduction heat transfer will flow to the neighbor area of the fractured zone. The results in this paper are pressure and enthalpy distribution as a time function at each depth.